Diskursus Publik Mengenai Regulasi Garam di Indonesia - Fallicia Evangeline, Maria; Anggono, Alexander; Tarjo (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2024)
This research examines Indonesia's dependence on salt imports and public discourse on salt regulation. Using Critical Discourse Analysis (CDA) and process tracing, this study examines the public discourse on the national salt regulation by highlighting shortcomings and public dissatisfaction. The study aims to understand public perceptions of the regulation, its impact on consumer and industry behavior, and the challenges and opportunities for stakeholders. The results show that the majority of public opinion is negative towards government regulations, indicating weaknesses in the implementation and effectiveness of regulations. These findings indicate that regulations are not yet optimal and require stricter enforcement and in-depth evaluation. The study suggests additional steps for the development of the local salt industry and the importance of coordination between the government, industry, salt farmers and other stakeholders for a successful national salt industry development strategy.